Spatiotemporally restricted arenavirus replication induces immune surveillance and type I interferon-dependent tumour regression - Halime Kalkavan (Nature Portfolio, 2017)
Viruses are promising anti-tumour therapeutics due to induction of an immune response and/or oncolytic activity. Here, Kalkavanet al. show that LCMV replicates in tumour cells, without inducing cell lysis, and that its anti-tumour activity is largely mediated by recruitment of interferon-producing monocytes.